First record and DNA barcodes of the aquarium shrimp, Neocaridina davidi, in Central Europe from thermally polluted River Oder canal, Poland - Jabłońska Aleksandra; Mamos Tomasz; Gruszka Piotr; Szlauer-Łukaszewska Agnieszka; Grabowski Michał (Knowledge and Management of Aquatic Ecosystems, 2018)
Neocaridina davidi (Bouvier, 1904) is an exotic freshwater shrimp originating from Asia and often kept as a pet in amateur aquarium cultures. Herewith, we report on the second finding of N. davidi in fresh waters of Europe and the first discovery of that species both in Poland and in Central Europe. The species was found in samples collected in 2003, 2013 and 2017 in the thermally polluted canal connected to the River Oder, south of Gryfino, in the vicinity of the Dolna Odra Power Plant. The taxonomic identity of the collected shrimp was confirmed by the standard DNA barcoding procedure, using a 610 bp-long fragment of cytochrome oxidase I (COI). The findings spanning more than a decade suggest that N. davidi may have established a self-reproducing population at this site. Following the finding of Atyaephyra desmarestii (Millet, 1831) in 2000, Neocaridina davidi is the second freshwater shrimp species found in the River Oder and in Poland.